Pemahaman Konsep Karakter Tanggung Jawab pada Mahasiswa PPKn FKIP UAD - Wiwik Okta Susilawati; Olga Frida Zwastikawati (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2021)
This study aims to determine the overall understanding of the concept of responsibility in students. This type of research is quantitative research. The research sample consisted of 51 students, who came from active students of the PPKn FKIP UAD class of 2012-2014 who had taken the Ethics course. Data collection was carried out through multiple choice test instruments. Before being used for research, the test instrument has been tested for validity and reliability first. The data analysis method used is descriptive statistical analysis. These results were obtained from one aspect, namely understanding the concept of responsibility for students. This aspect has a good tendency with the following descriptions: Interpreting responsibility (62.5%), exemplifying the attitude of responsibility (75.5%), classifying the kinds of responsibilities (57%), summarizing the indicators of responsibility (77.5 %), summed up the equations of personal, social, and responsibility towards God (63%), compared personal, social, and responsibility towards God Almighty (82%) and explained the concept of responsibility (39%).